Re-conceptualizing the Factor Structure of the Brief Multidimensional Measure of Religiousness/Spirituality - Johnstone, Brick (Journal of religion and health, 2009)
Rationale This study attempted to differentiate statistically the spiritual and religious factors of the Brief Multidimensional Measure of Religiousness/Spirituality (BMMRS), which was developed based on theoretical conceptualizations that have yet to be adequately empirically validated in a population with significant health disorders. Participants One hundred sixty-four individuals with heterogeneous medical conditions [i.e., brain injury, spinal cord injury (SCI), cancer, stroke, primary care conditions]. Methods Participants completed the BMMRS as part of a pilot study on spirituality, religion, and physical and mental health. Results A principal components factor analysis with varimax rotation and Kaiser normalization identified a six-factor solution (opposed to the expected 8-factor solution) accounting for 60% of the variance in scores, labeled as: (1) Positive Spiritual Experience; (2) Negative Spiritual Experience; (3) Forgiveness; (4) Religious Practices; (5) Positive Congregational Support; and (6) Negative Congregational Support. Conclusions The results suggest the BMMRS assesses distinct positive and negative aspects of religiousness and spirituality that may be best conceptualized in a psychoneuroimmunological context as measuring: (a) Spiritual Experiences (i.e., emotional experience of feeling connected with a higher power/the universe); (b) Religious Practices (i.e., prayer, rituals, service attendance); (c) Congregational Support; and (d) Forgiveness (i.e., a specific coping strategy that can be conceptualized as religious or non-religious in context).